EDUCATIONAL AND COGNITIVE ACTIVITY OF STUDENTS IN ACCORDANCE WITH THEIR PHYSICAL AND MENTAL DEVELOPMENT - Suvonov Kadyr Yoldoshevich (Journals Park Publishing, 2023)
This article explains the mechanisms of the development of mental abilities in the minds of students through engagement into physical culture and sports.
Keywords: physical and mental development, educational and cognitive activity, physical culture, conceptual framework.